Monetary factors and inflation in Japan - Katrin Assenmacher-Wesche; Stefan Gerlach; Toshitaka Sekine (Goethe University Frankfurt, Institute for Monetary and Financial Stability (IMFS), 2007)
Recently, the Bank of Japan outlined a “two perspectives” approach to the conduct of monetary policy that focuses on risks to price stability over different time horizons. Interpreting this as pertaining to different frequency bands, we use band spectrum regression to study the determination of inflation in Japan. We find that inflation is related to money growth and real output growth at low frequencies and the output gap at higher frequencies. Moreover, this relationship reflects Granger causality from money growth and the output gap to inflation in the relevant frequency bands. Keywords: spectral regression, frequency domain, Phillips curve, quantity theory.
urn:nbn:de:hebis:30-70439
Keywords: C22; E3; E5; 330; asset prices; monetary policy; panel VAR